2019
DOI: 10.4081/gh.2019.747
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol sale status and homicide victimization in Kentucky, 2005-2012: Is there a spatial association?

Abstract: To date, the association between the alcohol sale status of decedents’ residence and alcohol-related homicide victimization have not been studied as far as we know. The current study aims to: i) determine whether homicide victims who were residents of wet counties had higher odds of testing positive for alcohol than their counterparts in moist or dry counties after adjusting for confounders; ii) determine whether homicides and alcohol-related homicides tend to cluster spatially; iii) determine whether the afor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…A study in Kentucky, USA, examined the homicides rates at the county level and showed that homicide rates were higher in areas with high alcohol sales. The multilevel logistic regression was performed using clustered and non-clustered homicide areas as the binomial dependent variable; however, if the researchers had used the GWR method, the spatial association between homicide rates and independent variables would have been obtained [ 59 ]. Another study based on GIS and spatial analysis [ 60 ] showed that violent crimes and homicide rates were higher in areas where secondary schools and sport places were concentrated.…”
Section: Methodological Literature Reviewmentioning
confidence: 99%
“…A study in Kentucky, USA, examined the homicides rates at the county level and showed that homicide rates were higher in areas with high alcohol sales. The multilevel logistic regression was performed using clustered and non-clustered homicide areas as the binomial dependent variable; however, if the researchers had used the GWR method, the spatial association between homicide rates and independent variables would have been obtained [ 59 ]. Another study based on GIS and spatial analysis [ 60 ] showed that violent crimes and homicide rates were higher in areas where secondary schools and sport places were concentrated.…”
Section: Methodological Literature Reviewmentioning
confidence: 99%